Assessing the relevance of exposure time in differentiated Caco-2/HT29 cocultures. Effects of silver nanoparticles. (January 2019) - Saez-Tenorio, Miriam; Domenech, Josefa; García-Rodríguez, Alba; Velázquez, Antonia; Hernández, Alba; Marcos, Ricard; Cortés, Constanza
Abstract: In vitro models of the intestinal barrier are being increasingly used to evaluate nanoparticles (NPs) exposure risk. Nevertheless, most of these studies have focused on short-term exposures lasting no more than 24 h of duration, which could underestimate the toxic effects of a given compound under a more realistic setting. Since the assessment of longer exposure time-points is crucial to evaluate the risk of cumulative exposure to NPs, we have analyzed the effects of AgNPs at different exposure time-points between 6 h and 4 days on the barrier model system constituted by Caco-2/HT29 cells. Our results indicate that i) the system is stable during this time frame; ii) AgNPs affect the barrier's integrity only at the highest concentration tested (100 μg/mL), and only after 96 h of exposure; iii) cellular uptake of AgNPs showed a time-dependent and concentration-dependent increase; iv) translocation through the barrier was only observed at the highest concentration and only after 96 h of exposure; v) the expression of genes involved in the barrier's structure differs depending on the exposure time analyzed. All these results reinforce our proposal of expanding exposure times beyond 24 h when performing assays for hazard assessment of NPs using in vitro models of the intestinal barrier. Highlights: The Caco-2/HT29 model is stable during the 96 h time-frame. AgNPs affect barrier's integrity only at the highest concentration and longest exposure time. Translocation through the barrier was observed only at the highest concentration and longest exposure time. The expression of genes involved in the barrier's structure changed throughout the exposure time. Expanding exposure times beyond 24 h gives a wider perspective of long-term toxicity.